Analysis of serum calprotectin levels in ménière’s patients and investigation of its effect on disease severity - Hüseyin Işık; Deniz Baklaci; Tuba Candar; Duygu Erdem; Ergin Bilgin (PLoS ONE, 2026)
Objective This prospective observational study aimed to evaluate serum calprotectin levels in patients with definite Ménière’s Disease (MD) and to investigate their association with symptom duration and disease severity. Materials and methods Thirty-nine patients (16 males, 23 females; mean age 37.2 ± 11.9 years) diagnosed with definite MD according to the AAO–HNS criteria and 28 age- and sex-matched healthy controls (14 males, 14 females; mean age 39.2 ± 13.3 years) without vestibular or auditory complaints were included. Individuals with active infection, autoimmune or chronic inflammatory disease, recent antibiotic or steroid use, or other otologic pathologies were excluded. Serum calprotectin levels were measured during an acute vertigo attack in the MD group and once in controls. Between-group differences and correlations with clinical variables were analyzed using appropriate parametric and non-parametric tests. Results Mean serum calprotectin levels during acute attack were significantly higher in the MD group than in controls (1031 ± 364 vs. 611 ± 231 ng/mL, p < 0.001). Within the MD group, calprotectin levels showed a strong positive correlation with symptom duration (Spearman’s ρ = 0.914, p < 0.001). In patients with MD, calprotectin levels decreased significantly after treatment, from 1031 ± 364 to 582 ± 339 ng/mL (mean difference 449 ng/mL, 95% CI 353–545; t (38) = 9.46, p < 0.001; Cohen’s d = 1.51), indicating a large effec t size. Conclusion Patients with Ménière’s Disease exhibit elevated serum calprotectin levels during acute attacks, which correlate strongly with symptom duration and decrease significantly after treatment. These findings suggest that calprotectin may be a potential inflammatory biomarker associated with disease burden and treatment response in MD; however, longitudinal studies with larger cohorts are needed to determine its diagnostic and prognostic utility.